Gastric Mucosa-associated Lymphoid Tissue Lymphoma Mimicking Signet Ring Cell Carcinoma - Han Il Choi; Bong Eun Lee; Kyung Bin Kim; Gwang Ha Kim; Moon Won Lee; Dong Chan Joo (Yong Chan Lee, 2023)
Gastric mucosa-associated lymphoid tissue (MALT) lymphoma is the most common type of extranodal non-Hodgkin lymphoma. Endoscopic findings are nonspecific and variable; therefore, differentiation of this malignancy from early gastric cancer is challenging during endoscopy. Although an endoscopic biopsy is the gold standard for diagnosis, a biopsy may not conclusively establish the diagnosis in all cases. Diagnostic confirmation requires interpretation of the biopsy specimen findings by an experienced histopathologist, and an additional immunoglobulin heavy chain (IgH) rearrangement test may aid with accurate diagnosis. We present a case of gastric MALT lymphoma that histopathologically mimicked signet ring cell carcinoma (SRCC) on evaluation of repeat endoscopic biopsies. Following endoscopic submucosal dissection (ESD), we confirmed the final diagnosis of gastric MALT lymphoma based on histopathological findings of prominent lymphoid infiltrates accompanied by lymphoepithelial lesions and results of the monoclonal IgH rearrangement test. Notably, a few carcinoma-like signet ring cells (SRCs) in the specimen were attributed to a reactive change. Clinicians should be mindful of possible SRCs in gastric MALT lymphoma specimens to avoid misdiagnosis of SRCC in patients with gastric MALT lymphoma. Confirmatory ESD may be useful for accurate diagnosis and appropriate management of such lesions.